Canadian Stroke Best Practice Recommendations: Mood, Cognition and Fatigue following Stroke, 6th edition update 2019. Issue 6 (August 2020) - Lanctôt, Krista L; Lindsay, M Patrice; Smith, Eric E; Sahlas, Demetrios J; Foley, Norine; Gubitz, Gord; Austin, Melissa; Ball, Kristyn; Bhogal, Sanjit; Blake, Treena; Herrmann, Nathan; Hogan, David; et al.
The 2019 update of the Canadian Stroke Best Practice Recommendations (CSBPR) for Mood, Cognition and Fatigue following Stroke is a comprehensive set of evidence-based guidelines addressing three important issues that can negatively impact the lives of people who have had a stroke. These include post-stroke depression and anxiety, vascular cognitive impairment, and post-stroke fatigue. Following stroke, approximately 20% to 50% of all persons may be affected by at least one of these conditions. There may also be overlap between conditions, particularly fatigue and depression. If not recognized and treated in a timely matter, these conditions can lead to worse long-term outcomes. The theme of this edition of the CSBPR is Partnerships and Collaborations, which stresses the importance of integration and coordination across the healthcare system to ensure timely and seamless care to optimize recovery and outcomes. Accordingly, these recommendations place strong emphasis on the importance of timely screening and assessments, and timely and adequate initiation of treatment across care settings. Ideally, when screening is suggestive of a mood or cognition issue, patients and families should be referred for in-depth assessment by healthcare providers with expertise in these areas. As the complexity of patients treated for stroke increases, continuity of care and strong communication among healthcare professionals, and between members of the healthcare team and the patient and their family is an even bigger imperative, as stressed throughout the recommendations, as they are critical elements to ensure smooth transitions from acute care to active rehabilitation and reintegration into their community.